A Study of Space – Time Conceptual Metaphor in English= Nghiên cứu ẩn dụ ý niệm không gian - thời gian trong tiếng Anh (Chương trình loại 1). M.A Thesis Linguistics: 60 14 10 - Nguyễn, Thị Phương Nhung (2019)
This study investigates into the space - time conceptual metaphor in English, which the abstract domain of time gets its relational structure from the more concrete domain of space through metaphorical mappings. The research focuses on two spatial prepositions before and behind in the light of cognitive perspective. Hence, the meanings of these two particles are clarified through the analysed image schemas and two moving models.